Manfaat Penerapan Metode AON (Activity On Node) untuk Penjadwalan Proyek Bangunan Bertingkat Tinggi - rachmi yanita; Intan F Ningrum; Krishna Mochtar (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2020)
The construction project is assessed based on the realization of the construction according to the quality, time and cost in the planning document. To monitor implementation, a scheduling method is needed that can describe the relationship between activities and implementation time, so that the work can be completed according to the target duration specified in the construction contract. Two methods are known in scheduling critical paths, namely Activity On Arrow (AOA) and Activity On Node (AON) where AOA is more widely used in projects, whereas AON has the advantage of 4 relationships between activities with activity symbols on the box, while AOA is only 1 type with symbol of the activity on the arrow. The purpose of this study is to obtain the benefits of using AON rather than AOA by scheduling using the two methods on the schedule of the construction of a high-rise building in Banten, using Microsoft Project (MS Project) software, and analyzing the differences. In MS Project AOA is known as the Activity Diagram Method and AON with the Precedence Diagram Method. From the comparative analysis results obtained that with AOA obtained 74 activities and 48 activities with AON with the same duration and critical activities in both methods. The AON diagram can better illustrate the relationship between activities that are simpler and simpler with a total efficiency of 35%. Keyword: AOA, AON, relationship between activities, scheduling method